MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SDN 4 SIBAKUR MELALUIMELALUI MODEL COOPERATIF LEARNING - Sumiati Sumiati (JOURNAL OF COMMUNITY DEDICATION, 2024)
This study aims to determine the impact of applying the Cooperative Learning model Student Teams-Achievment Division (STAD) on improving learning motivation in Islamic Education for fourth-grade students at SD Negeri 4 Sibakur, Tanjung Gadang District. The problem faced is the low motivation and learning outcomes of students in Islamic Education and Character Education subjects, caused by the monotonous lecture method. This research uses a Classroom Action Research (CAR) design with two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study are 12 fourth-grade students. The instruments used include observation sheets, learning motivation questionnaires, and test results. The findings show that the implementation of the Cooperative Learning model can improve students' learning motivation. This is evident from the increased activity and involvement of students in the learning process, as well as better learning outcomes after applying the model. This study concludes that the Cooperative Learning model is effective in improving students' motivation and learning outcomes in Islamic Education. Therefore, it is recommended for teachers to use this method to create a more active and engaging learning environment.